Mental disorders, disability and treatment gap in a protracted refugee setting. (March 2014) - Llosa, Augusto E.; Ghantous, Zeina; Souza, Renato; Forgione, Fabio; Bastin, Pierre; Jones, Alison; Antierens, Annick; Slavuckij, Andrei; Grais, Rebecca F.
Abstract : Background: Studies have shown high levels of distress and mental disorder among people living in refugee camps, yet none has confirmed diagnosis through clinical reappraisal. Aims: To estimate the prevalence of mental disorders, related disability and treatment gap in adult refugees living in the Burj el-Barajneh camp. Method: Randomly selected participants were screened by household representative ( n = 748) and individual ( n = 315) interviews; clinical reappraisal was performed on a subset ( n = 194) of 326 selected participants. Weighted prevalence estimates and 95% confidence intervals were calculated. Results: The prevalence of current mental disorders was 19.4% (95% CI 12.6–26.2); depression was the most common diagnosis (8.3%, 95% CI 4.4–12.2) and multiple diagnoses were common (42%) among the 88 persons with mental disorder. Lifetime prevalence of psychosis was 3.3% (95% CI 1.0–5.5). Mental disorders were associated with moderate to severe dysfunction (odds ratio = 8.8, 95% CI 4.5–17.4). The treatment gap was 96% (95% CI 92–100). Conclusions: A range of mental disorders and associated disability are common in this long-term refugee setting. Combined with an important treatment gap, findings support the current consensus-based policy to prioritise availability of mental health treatment in refugee camps, especially for the most severe and disabling conditions.